Una Revisión de la generación automática de resúmenes extractivos (2013)
Research in the area of automatic text summarization has intensifed in recent years due to the large amount of information available in electronic documents. This article present the most relevant methods for automatic text extractive summarization that have been developed both for a single document and multiple documents, with special emphasis on methods based on algebraic reduction, clustering and evolutionary models, of which there is great amount of research in recent years, since they are language-independent and unsupervised methods.